Conversing the audience: A methodological exploration of how conversation analysis can contribute to the analysis of interactive journalism. (December 2014) - Steensen, Steen
This paper argues that conversation analysis (CA) has much to offer studies of online interactions and, particularly, online interactive journalism. CA provides a methodological opportunity to closely investigate the structure of public discourse in new media platforms, and power relations between journalists and audiences in instances of interactive journalism. The paper introduces CA and discusses how it may be combined with other methods in order to pinpoint the characteristics of online interactions in general and interactive journalism in particular. In the second half of the paper, the CA-inspired methodological approach used to analyse a case study of an interactive live blog in the Norwegian online newspaper VG Nett is presented.